2000
DOI: 10.1177/088307380001500510
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Study of Children With Sickle Cell Disease: Radiographic and Psychometric Correlation

Abstract: After obtaining familial informed consent, between January 1996 and July 1997, 173 children (5 to 15 years old) with sickle cell disease were enrolled in a prospective multicenter study using blood screening, transcranial Doppler ultrasonography (n = 143), cerebral magnetic resonance imaging (n = 144), and neuropsychologic performance evaluation (n = 156) (Wechsler Intelligence tests WISC-III, WIPPSI-R), which were also performed in 76 sibling controls (5 to 15 years old). Among the 173 patients with sickle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
237
3
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(255 citation statements)
references
References 19 publications
9
237
3
6
Order By: Relevance
“…This percentage is similar to the percentage reported in a French study [5] and is expected to have profound consequences for academic functioning. It is surprising to note; however, that relatively few children with SCD in our sample (14%) received special educational services.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This percentage is similar to the percentage reported in a French study [5] and is expected to have profound consequences for academic functioning. It is surprising to note; however, that relatively few children with SCD in our sample (14%) received special educational services.…”
Section: Discussionsupporting
confidence: 87%
“…Children with SCD and overt strokes seem to be most impaired, with a decrease of approximately 14 Full-scale IQ points [3], while children with silent infarcts have been described to score 4-7 Full-scale IQ points lower than children with normal MRI [4,5]. However, it appears that there are cognitive effects of SCD for children with normal MRI as well [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the only method to detect SCI. Children with a previous SCI are at increased risk for stroke, new or enlarging silent cerebral infarcts [81], poor academic achievement [82], and lower performance on intelligence tests when compared with children with SCA with normal neuroimaging, or children without SCA [83]. Based on the morbid and progressive nature of SCI, the NINDS sponsored the Silent Infarct Transfusion (SIT) trial, a multicenter randomized trial in which children with SCA and SCI were assigned to receive standard care (observation group) or regular blood-transfusion therapy (transfusion group).…”
Section: Stroke Prevention In Scamentioning
confidence: 99%
“…The much higher burden of stroke in adults compared with children with SCD may be due to the widespread use of TCD screening coupled with regular blood transfusion therapy in children with SCA, as well as the growing adult SCD population. Survivors of overt stroke demonstrate global neurocognitive impairment [103]; and multiple prospective studies have identified lower IQ scores, learning difficulties, and impairment of executive function in children without strokes and with normal imaging studies [83,103,104]. These neurological impairments increase with age [103].…”
Section: Pulmonary Complicationsmentioning
confidence: 99%
“…In Memphis, the stroke rate decreased from 0.46 to 0.18 per 100 person-years after the TCD screening rate reached 99% [25]. In a newborn SCA-cohort of Creteil, France, including 217 SS/Sβ0 thalassaemia patients, early and annually screened with TCD since 1992, the cumulative stroke risk by age 18 was 1.9% (95% CI, 0.6-5.9) [14,26,27]. In Philadelphia, the incidence of overt stroke in the post-TCD period was 0.06 per 100 patient-years, compared with 0.67 per 100 patient-years in the pre-TCD period [28].…”
Section: Indicationsmentioning
confidence: 99%